Introduction to sensors for electrical and mechanical engineers - Novák, Martin, 1982- (CRC Press, Taylor & Francis Group, 2021)
"The objective of this book is to provide the basic knowledge to electrical and mechanical engineers, engineering students and hobbyist from the field of sensors to help them with the selection of "proper" sensors for their designs. No background knowledge in electrical engineering is required, all the necessary basics are provided. The book explains how a sensor works, in what ranges it can be used, with what accuracy etc. It also provides examples of industrial application for selected sensors. The book covers all the major variables in mechanical engineering such as temperature, force, torque, pressure, humidity, position, speed, acceleration etc"- Resumé vydavatel